(untitled) (International Journal of Health, Animal Science and Food Safety, 2015)
Anthrax is caused by the organism Bacillus anthracis. The organism is globally occurring and epidemics are reported the world over. It is an important infectious disease of domestic animals and can survive harsh conditions that would otherwise be drastic for other microorganisms. To date, no outbreak has been reported in the Pacific Island region except Australia and New Zealand where B. anthracis has been isolated from livestock. Papua New Guinea has had sporadic (reported) instances of anthrax outbreak, but has not been scientifically established. It is still unclear if the anthrax causing organism is present in the environment or wildlife in the country. It remains to be so until scientific evidence becomes available. This article aims to review scientific evidence of anthrax in the country.